2010
DOI: 10.1371/journal.pone.0013755
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Immunogenicity Following Administration of a Live, Attenuated Monovalent 2009 H1N1 Influenza Vaccine to Children and Adults in Two Randomized Controlled Trials

Abstract: BackgroundThe safety, tolerability, and immunogenicity of a monovalent intranasal 2009 A/H1N1 live attenuated influenza vaccine (LAIV) were evaluated in children and adults.Methods/Principal FindingsTwo randomized, double-blind, placebo-controlled studies were completed in children (2–17 y) and adults (18–49 y). Subjects were assigned 4∶1 to receive 2 doses of H1N1 LAIV or placebo 28 days apart. The primary safety endpoint was fever ≥38.3°C during days 1–8 after the first dose; the primary immunogenicity endpo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
39
0
5

Year Published

2011
2011
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(46 citation statements)
references
References 33 publications
2
39
0
5
Order By: Relevance
“…This provided an opportunity to assess not only the vaccines' immunogenicity, but also their clinical efficacy. Both LAIVs were tested in randomized, placebocontrolled trials in adults and children shortly after the pandemic was declared [56,57]. As expected, the vaccines were found to be safe and well tolerated by both age groups.…”
Section: The 2009 H1n1pdm Laivsmentioning
confidence: 69%
“…This provided an opportunity to assess not only the vaccines' immunogenicity, but also their clinical efficacy. Both LAIVs were tested in randomized, placebocontrolled trials in adults and children shortly after the pandemic was declared [56,57]. As expected, the vaccines were found to be safe and well tolerated by both age groups.…”
Section: The 2009 H1n1pdm Laivsmentioning
confidence: 69%
“…The published AE rates vary greatly (0.2---41.7% of all vaccinated individuals), depending particularly on the study population and on the vigilance system involved. 171,172 The incidence density varies between 9 and 31.8 AEs for every 100,000 administered doses. Problems in this sense are more frequent in the first 24 h after vaccination in the younger population, and there are no gender differences.…”
Section: Side Effectsmentioning
confidence: 99%
“…Functional serum antibody titers as measured by HAI are generally regarded as a correlate of protection for inactivated influenza vaccines. However, studies have demonstrated that LAIV can induce protection from influenza illness in the absence of robust serum antibody responses, as measured by fourfold rises in HAI [42][43][44][45]. Mucosal [46] and cell-mediated immune responses [47] are important contributors to LAIV-induced immunity; however, these responses are difficult to measure, and there are no standard or widely accepted assays.…”
Section: Immunogenicity Of Q/laivmentioning
confidence: 99%